2014
DOI: 10.2147/nss.s53721
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and psychomotor vigilance task performance

Abstract: BackgroundObstructive sleep apnea (OSA) is a highly prevalent disorder with considerable morbidity and mortality. Vigilance and attentiveness are often impaired in OSA patients. In occupational medicine settings, subjective reports of sleepiness are notoriously inaccurate, making the identification of objective measures of vigilance potentially important for risk assessments of fitness for duty. In order to evaluate the effects of OSA on attentiveness and vigilance, we conducted a cross-sectional study to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…In contrast to ESS, the PVT is sensitive to both acute (Doran et al ., ) and chronic partial sleep deprivation (Dinges et al ., ). Therefore, while our results are consistent with other data in clinical settings (Batool‐Anwar et al ., ), ESS may not predict acute situational compromises in persons who are acutely sleep deprived, but not chronically so. This problem is ameliorated by the findings of multiple operational studies though, showing that military populations are chronically sleep deprived (Miller et al ., , , ).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to ESS, the PVT is sensitive to both acute (Doran et al ., ) and chronic partial sleep deprivation (Dinges et al ., ). Therefore, while our results are consistent with other data in clinical settings (Batool‐Anwar et al ., ), ESS may not predict acute situational compromises in persons who are acutely sleep deprived, but not chronically so. This problem is ameliorated by the findings of multiple operational studies though, showing that military populations are chronically sleep deprived (Miller et al ., , , ).…”
Section: Discussionmentioning
confidence: 94%
“…PVT is one of the leading assays of sustained attention in the sleep‐related research and is highly sensitive to the effect of sleep loss (Deurveilher, Bush, Rusak, Eskes, & Semba, ). Studies in rats of chronic sleep restriction or sleep deprivation and in patients with sleep–wake disorders or obstructive sleep apnea showed that poorer PVT performance was associated with more sleep loss and excessive daytime sleepiness (Batool‐Anwar et al., ; Deurveilher et al., ; Dinges et al., ; Doran, Van Dongen, & Dinges, ; Oonk, Davis, Krueger, Wisor, & Van Dongen, ; Thomann, Baumann, Landolt, & Werth, ). Insomniacs often complain about insufficient sleep and sleepiness in the daytime that make daytime alertness and sustained attention impaired.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] It has been shown that sleepiness, as a result of chronic sleep restriction or total sleep deprivation, is associated in a dose-response manner with impaired PVT performance. 13 Dinges and colleagues reported that sleep restriction to 4 to 5 hours per night for 1 week resulted in significantly elevated subjective daytime sleepiness (as measured by the Stanford Sleepiness Scale) and progressive deterioration of PVT performance across the days of restricted sleep.…”
Section: Introductionmentioning
confidence: 99%